2017
DOI: 10.1002/2017wr020839
|View full text |Cite
|
Sign up to set email alerts
|

Solving water quality problems in agricultural landscapes: New approaches for these nonlinear, multiprocess, multiscale systems

Abstract: Changes in climate and agricultural practices are putting pressure on agroenvironmental systems all over the world. Predicting the effects of future management or conservation actions has proven exceptionally challenging in these complex landscapes. We present a perspective, gained from a decade of research and stakeholder involvement in the Minnesota River Basin, where research findings have influenced solutions and policy in directions not obvious at the outset. Our approach has focused on identifying places… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 34 publications
0
19
0
Order By: Relevance
“…Because land use appears to have most influence on TSS concentrations at low and moderate flows, regulations on land use aimed at reducing erosion from upland soils may be most effective at reducing TSS during those flow conditions. However, if the near‐channel geomorphic environment determines the shape and steepness of the relations, then TSS reduction at high flows may be best achieved by management approaches aimed at reducing the frequency and magnitude of high flows in order to control erosion from near‐channel sources (Belmont et al, ; Belmont & Foufoula‐Georgiou, ).…”
Section: Management Implicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Because land use appears to have most influence on TSS concentrations at low and moderate flows, regulations on land use aimed at reducing erosion from upland soils may be most effective at reducing TSS during those flow conditions. However, if the near‐channel geomorphic environment determines the shape and steepness of the relations, then TSS reduction at high flows may be best achieved by management approaches aimed at reducing the frequency and magnitude of high flows in order to control erosion from near‐channel sources (Belmont et al, ; Belmont & Foufoula‐Georgiou, ).…”
Section: Management Implicationsmentioning
confidence: 99%
“…Suspended sediment concentrations measured at a given location are influenced by sediment sources and sinks upstream of that point and are therefore expected to depend on watershed characteristics such as geology, climate, vegetative cover, rainfall intensity, slope, topographic relief, and human impacts (Ahnert, ; Ali & de Boer, ; de Vente et al, ; Langbein & Schumm, ); Mueller & Pitlick, ; Summerfield & Hulton, ; Syvitski et al, ; Syvitski & Milliman, ; Wischmeier & Smith, ; Verstraeten & Poesen, ). Recent studies have demonstrated that the near‐channel environment may also be a dominant factor contributing sediment to streams, even in agricultural watersheds (Belmont et al, ; Belmont & Foufoula‐Georgiou, ; Czuba et al, ; Donovan et al, ; Foufoula‐Georgiou et al, ; Lenhart et al, ; Stout et al, ; Walter & Merritts, ). Determining the relative importance of watershed versus near‐channel features in predicting riverine sediment fluxes remains a challenge in Earth surface science.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though artificial drainage reduces field erosion by reducing surface runoff, it has been shown to essentially have shifted the sediment source from fields to channels (Belmont, 2011;Belmont and Foufoula-Georgiou, 2017). Basins experiencing increases in streamflow due to natural (climate) and anthropogenic (drainage) factors have increased stream power available to erode and transport more sediments and sediment bound nutrients and contaminants.…”
Section: Interpretations Implications and Conclusionmentioning
confidence: 99%
“…Less research has focused on the implications of hydrologic change for sediment loads in agricultural landscapes. For waters impaired by sediment under the US Clean Water Act (CWA), EU Water Framework Directive, and similar regulations around the world, loads often consist of both natural and human-derived sediment sources Gran et al, 2011;Belmont and Foufoula-Georgiou, 2017). Differentiating between these two sources is often very difficult, and yet is essential for identifying and achieving water quality standards Trimble and Crosson, 2000;Wilcock, 2009).…”
Section: Introductionmentioning
confidence: 99%